“For livmoderen er en slags forunderlighedernes værksted” – Thomas Bartholin, forplantningen og den legende natur - Nipper Nielsen, Signe (Slagmark - Tidsskrift for idéhistorie, 2019)
“FOR THE UTERUS IS A SORT OF WORKSHOP OF WONDERS”: THOMAS BARTHOLIN, GENERATION AND THE JOKES OF NATURE By focusing on the topic of generation, i.e. the engendering of new individuals, this article examines the “stuff” of nature, observed by empirical medicine in the 17 th century, represented by a renowned Danish anatomist, Thomas Bartholin (1616-1680). Bartholin represented the surge in empirical approaches to natural inquiry in the early modern period, and corresponded about and collected and exchanged a large number of written observations and anatomical and zootomical objects related to the workings of the female body and the process of generation. It is the main argument of this article that through this type of scientific observation, the human procreative body emerged as abundant, limitless and transformative, and its products became expressions of nature’s creativity. Bartholin described throughout his oevre numerous extraordinary products of generation, ranging from monstrous births to plants and animals generated inside human bodies, as illustrations of the ‘jokes of nature’ (lusus naturæ), a conceptual legacy from ancient literature and natural history denoting nature’s ingenuity and excessiveness, unbound by regularity and order.